Vasomotor symptoms and the risk of incident venous thrombosis in postmenopausal women. (2nd April 2018) - Harrington, L. B.; Blondon, M.; Cushman, M.; Kaunitz, A. M.; Allison, M. A.; Wang, L.; Sullivan, S.; Woods, N. F.; LaCroix, A. Z.; Heckbert, S. R.; McKnight, B.; Rossouw, J.; et al.
Abstract : Essentials Vasomotor symptoms have been proposed as markers of changing cardiovascular risk. In this cohort study, we evaluated these symptoms as markers of venous thrombosis (VT) risk. We found no evidence that vasomotor symptom presence or severity were associated with VT risk. Among these postmenopausal women, vasomotor symptoms are not a useful marker of VT risk. Summary: Background: Vasomotor symptoms may be markers of changes in cardiovascular risk, but it is unknown whether these symptoms are associated with the risk of venous thrombosis (VT). Objective: To evaluate the association of vasomotor symptom presence and severity with incident VT risk among postmenopausal women, independent of potential explanatory variables. Methods: This cohort study included participants of the Women's Health Initiative (WHI) Hormone Therapy Trials ( n = 24 508) and Observational Study ( n = 87 783), analyzed separately. At baseline, women reported whether hot flashes or night sweats were present and, if so, their severity. Using Cox proportional hazards models, we estimated the VT risk associated with vasomotor symptom presence and severity, adjusted for potential explanatory variables: age, body mass index, smoking status, race/ethnicity, and time‐varying current hormone therapy use. Results: At baseline, WHI Hormone Therapy Trial participants were aged 64 years and WHI Observational Study participants were aged 63 years, on average. In the WHI Hormone Therapy Trials over a median of 8.2 years of follow‐up, 522 women experienced a VT event. In the WHI Observational Study, over 7.9 years of follow‐up, 1103 women experienced a VT event. In adjusted analyses, we found no evidence of an association between vasomotor symptom presence (hazard ratio [HR]adj 0.91, 95% confidence interval [CI] 0.75–1.1 in the WHI Hormone Therapy Trials; HRadj 1.1, 95% CI 0.99–1.3 in the WHI Observational Study) or severity (HRadj for severe versus mild 0.99, 95% CI 0.53–1.9 in the WHI Hormone Therapy Trials; HRadj 1.3, 95% CI 0.89–2.0) in the WHI Observational Study) and the risk of incident VT. Conclusions: Although vasomotor symptoms have been associated with the risk of other cardiovascular events in published studies, our findings do not suggest that vasomotor symptoms constitute a marker of VT risk.